Cognitive Decline in Prodromal Alzheimer's Disease and Mild Cognitive Impairment - Wilson, Robert S. (2011)
OBJECTIVE: To characterize the course of cognitive decline during the prodromal phase of Alzheimer's disease. DESIGN: Longitudinal cohort study with up to 16 years of observation. PARTICIPANTS: Older persons from two projects underwent annual clinical evaluations that included cognitive function testing and clinical classification of mild cognitive impairment, dementia, and Alzheimer's disease. At baseline, there were 2,071 individuals without dementia and 1,511 without cognitive impairment. MAIN OUTCOME MEASURES: Change in previously established composite measures of global cognition and specific cognitive domains assessed in mixed-effects models that allow rate of decline to shift at specific points. RESULTS: During follow-up, 462 persons developed Alzheimer's disease (20 with dementia solely due to another condition were excluded). Five to six years before the diagnosis, rate of global cognitive decline sharply accelerated by more than 15-fold. The acceleration in decline occurred slightly earlier for semantic memory (76 months before diagnosis) and working memory (75 months) than other cognitive functions. Mild cognitive impairment was also preceded by years of cognitive decline which began earlier (80 months before diagnosis) and proceeded more rapidly (annual loss of 0.102 unit) in the amnestic than nonamnestic (62 months, 0.072 unit) subtype. CONCLUSION: Dementia due to Alzheimer's disease is preceded by about five to six years of accelerated decline in multiple cognitive functions. By contrast, little decline is evident in persons not developing Alzheimer's disease.